Meningkatkan Kesadaran Politik Masyarakat dalam Mengadapi Tantangan Globalisasi Melalui Pendidikan Politik di SMK N 1 Jayapura - Ode Jamal; Emanuel Goo (Jurnal DIKMAS, 2021)
Political education is an important tool in increasing political awareness of the community, especially in the challenging era of globalization. This study aims to explore how political education at SMK N 1 Jayapura can contribute to increasing political awareness of students and the surrounding community. The method used is a qualitative approach with data collection through interviews, observations, and documentation studies. The results of the study indicate that structured political education can improve students' understanding of political issues and globalization, and encourage them to actively participate in the democratic process.